Contemporary Methods in Bioinformatics and Biomedicine and Their Applications - Sotirov, Sotir S.; Pencheva, Tania; Kacprzyk, Janusz; Atanassov, Krassimir T.; Sotirova, Evdokia; Staneva, Galya; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book gathers selected papers from the First International Symposium on Bioinformatics and Biomedicine. Issues related to medicine and health care constitute one of the grand challenges faces by the mankind, and this naturally implies a growing interest in these problems among both researchers and scholars, politicians and policymakers, as well as economist. The present values which gather selected papers from the First International Symposium on Bioinformatics and Biomedicine (BioInfoMed$1 (B2020) is a recent response to this interests. In the subsequent sections and chapters, it covers a multitude of various topics related to bioinformatics, biomedicine, bioenginering, as well as a broadly perceives healthcare. Issues related to decision making in bioinformatics, biomedicine and health care, mathematical modelling in biomedicine and health care, artificial intelligence in biomedicine and health care, uncertainty and imprecision, notably intuitionistic fuzzy sets with applications in bioinformatics and biomedicine, biomedical approaches and applications, biomedical imaging and image processing, and excitable structures and motor activity are covered.s
Keywords: Biomedical engineering; Bioinformatics; Biomedical Engineering and Bioengineering; Bioinformatics; Computational Biology; Biomedical Engineering; Congress